Hubungan Kebiasaan Makan dan Aktivitas Olahraga Terhadap Status Gizi Mahasiswa Semester V Prodi DIII Kebidanan STIK Siti Khadijah Palembang - Fristika, Yessy Octa (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
One way to assess a woman's health is to look at her nutritional status. Nutritional status is a measure of success in meeting nutritional needs. The nutrients you get come from the food you consume every day. Teenagers need to pay attention to eating habits because they will affect their growth as well as exercise habits. This research aims to see the relationship between eating habits and sports activities on the nutritional status of fifth semester students of the D-III Midwifery Study Program at STIK Siti Khadijah Palembang. This research uses a quantitative analytical design using primary data using a cross sectional approach. The research sample was taken by total sampling. The number of samples in this research was 38 samples. There is a significant relationship between Eating Habits and Sports Activities, namely P-Value 0.000. The results of this study are recommended for other researchers who intend to conduct research on the relationship between eating habits and sports activities on nutritional status by involving more samples and variables studied with different designs and using instruments that have standard validity and reliability values.